Співвідношення понять текст, твір і дискурс у сучасній лінгвістиці - Романишин, Наталія; Голтвян, Валентина (Видавництво Львівської політехніки, 2015)
Тhe article focuses on the different aspects of terms “text”, “discourse” and “literary work” as the notions of literary criticism, cognitive poetics, communicative linguistics; their definitions and understanding.
Keywords: текст; дискурс; художній твір